Transient Stability of Epigenetic Population Differentiation in a Clonal Invader - Shi, Wen; Chen, Xiaojie; Gao, Lexuan; Xu, Cheng-Yuan; Ou, Xiaokun; Bossdorf, Oliver; Yang, Ji; Geng, Yupeng (Frontiers in Plant Science, 2019)
Epigenetic variation may play an important role in how plants cope with novel environments. While significant epigenetic differences among plants from contrasting habitats have often been observed in the field, the stability of these differences remains little understood. Here, we combined field monitoring with a multi-generation common garden approach to study the dynamics of DNA methylation variation in invasive Chinese populations of the clonal alligator weed (Alternanthera philoxeroides). Using AFLP and MSAP markers, we found little variation in DNA sequence but substantial epigenetic population differentiation. In the field, these differences remained stable across multiple years, whereas in a common environment they were maintained at first but then progressively eroded. However, some epigenetic differentiation remained even after 10 asexual generations. Our data indicate that epigenetic variation in alligator weed most likely results from a combination of environmental induction and spontaneous epimutation, and that much of it is neither rapidly reversible (phenotypic plasticity) nor long-term stable, but instead displays an intermediate level of stability. Such transient epigenetic stability could be a beneficial mechanism in novel and heterogeneous environments, particularly in a genetically impoverished invader.